2016
DOI: 10.1159/000452568
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of p38 MAPK to the Ameliorating Effect of Enriched Environment on the Cognitive Deficits Induced by Chronic Cerebral Hypoperfusion

Abstract: Background/Aims: An enriched environment (EE) ameliorates learning and memory impairments induced by chronic cerebral hypoperfusion, and the p38 mitogen-activated protein kinase (p38 MAPK) signaling pathway exerts both beneficial and deleterious effects on the nervous system during the progression of ischemia. Methods: The present study investigated whether p38 MAPK participates in the process by which EE exposure ameliorates the cognitive deficits induced by chronic cerebral hypoperfusion. Results: EE exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…As shown in Figure 6C and supplementary Figure 3, both activated and total levels of P38 were upregulated but only in Braak VI stages, suggesting a neuroinflammatory environment at the level of the OB. In line with this findings, recent studies have shown that the activation of this pathway may lead neuronal apoptosis and functional deficits in vascular dementia [57]. In accordance, stage-specific alterations were also found for both activated and total levels of SEK1, again demonstrating altered cell-stress responses at olfactory level during MixD disorders.…”
Section: Olfactory Molecular Routes Disrupted In Mixd: Specificity Analysis Respect To the Ob Deregulated Proteome Observed In Pure Adsupporting
confidence: 81%
“…As shown in Figure 6C and supplementary Figure 3, both activated and total levels of P38 were upregulated but only in Braak VI stages, suggesting a neuroinflammatory environment at the level of the OB. In line with this findings, recent studies have shown that the activation of this pathway may lead neuronal apoptosis and functional deficits in vascular dementia [57]. In accordance, stage-specific alterations were also found for both activated and total levels of SEK1, again demonstrating altered cell-stress responses at olfactory level during MixD disorders.…”
Section: Olfactory Molecular Routes Disrupted In Mixd: Specificity Analysis Respect To the Ob Deregulated Proteome Observed In Pure Adsupporting
confidence: 81%
“…Mounting studies have suggested that exposure to EE treatment after brain injury leads to neuroprotective effects in animal models [9, 10]. Recently, EE treatment has been translated into a rehabilitation strategy for poststroke patients in the clinical setting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Enriched environment (EE) is an effective rodent rehabilitation treatment method, in which several animals are accommodated in a large space equipped with various toys and receive more sensorial movements, perceptions and social stimulation than in standard conditions. EE has a neuroprotective effect on animal models of cerebral ischemia 4 . There is significant evidence that EE also benefits the clinical rehabilitation of post-stroke patients, including promoting greater exercise, social interaction and personal control 5 .…”
Section: Introductionmentioning
confidence: 98%